Impact of Foreign and Domestic Order Imbalances on Return and Volatility-volume Relation - Irwan Adi Ekaputra (Asian Academy of Management Journal of Accounting and Finance, 2014)
Innovating from Chan and Fong (2000), this paper decomposes order imbalance into foreign and domestic order imbalances. Foreign and domestic order imbalances significantly affect the daily variation of returns in the Indonesian Market. The impact of foreign order imbalance is more pronounced in larger-cap stocks, while domestic order imbalance is more significant in smaller-cap stocks. Using both absolute residuals and realized volatility as measures of volatility, this study finds the number of trades to be the primary factor in volatility-volume relations, supporting Jones, Kaul and Lipson (1994). Consistent with previous research in more developed markets, this study also finds that absolute order imbalance does not explain realized volatility.